Mémoires vivantes et archives d’un espoir déçu - Frédéric Caille; Alexandre Mouthon (Revue Internationale des Études du Développement)
In the debate on climate change and alternatives to fossil fuels, experiments with renewable energies are “political objects”. Their results question the place of technology in foreign policy and in development aid, as well as the energy choices made by the countries of the North. To understand the solar installations of the Sofretes, installed in several countries in the South in the 1970s and 1980s, it was necessary to “invent” solar archives. By recounting the investigation, we show how, by relying on a relationship of trust and exchange with witnesses still alive, it renews the historiography of solar energy and opens new perspectives for political history.